Initial impact of Brexit on Ireland-UK trade flows - Eimear Flynn; Janez Kren; Martina Lawless (The Economic and Social Research Institute (ESRI), 2021)
This paper examines the early months of post-Brexit trade flows in goods between Ireland and the United Kingdom. Controlling for product-level time effects across all global trade partners, we isolate the contribution of Brexit to trade in the first eight months of 2021 from other potential common drivers of trade flows including the COVID-19 pandemic. The estimated direct impact of Brexit is highly asymmetric, reducing imports from the UK to Ireland substantially but without any statistically significant impact on exports. This is likely due to the gradual implementation of customs procedures by the UK, with a range of checks to be introduced in 2022. We decompose the Irish-UK trade flows into trade with Northern Ireland separately from Great Britain. This shows that all of the decline in trade is driven by Great Britain with the majority of the reduction attributable to Brexit. In contrast, trade between Ireland and Northern Ireland trade has increased considerably.
Keywords: F10; 330; Brexit; free trade agreements; customs checks